Effect of Compensation, Work Environment, and Teamwork on Employee Loyalty of PT Agung Berkat Bintatar Abadi - Zufri Kholis Pulungan; Rindi Andika (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect that compensation (X1), work environment (X2), and teamwork (X3) had on employee loyalty (Y) at PT Agung Berkat Bintatar Abadi. The population for this study comprised all 78 workers of PT Agung Berkat Bintatar Abadi. The sample size was calculated to be 78 respondents. This study took place in 2022. This study analyzed quantitative data using SPSS multiple linear regression models. The findings indicated that salary, work environment, and teamwork all had a favorable and substantial influence on PT Agung Berkat Bintatar Abadi's employee loyalty, both partly and concurrently. Compensation was the most influential factor in determining employee loyalty. Employee loyalty can be attributed to compensation, work environment, and teamwork 95.6 percent of the time, with the remainder attributed to other factors. Employee loyalty was inversely related to salary, work environment, and teamwork.